Effects of dietary supplementation of Trichoderma pseudokoningii fermented enzyme powder on growth performance, intestinal morphology, microflora and serum antioxidantive status in broiler chickens - Wei Chih Lin; Min Ting Lee; Chaur Tsuen Lo; Shen Chang Chang; Tzu-Tai Lee (Italian Journal of Animal Science, 2018)
This study was conducted to evaluate the dietary supplementation of Trichoderma pseudokoningii enzyme powder (EP) and its effect on the growth performance, intestinal morphology and antioxidative status of broilers. In vitro experiments showed that xylanase and cellulase activities of EP were 487.96 ± 14.14 U/g and 18.55 ± 0.54 U/g, respectively. Total phenolic and ferulic acid content was 4.79 ± 0.35 mg GAE/g DW and 4.38 ± 0.32 μM/g DW, respectively. A total of 240 d-old Ross 308 male broiler chicks were randomly subjected to one of four treatments, namely diets supplemented with dry EP at 0% (control), 0.1%, 0.2% or 0.4% for 35d. Results showed that in the starter phase (1–21 d), the EP supplemented groups had improved body weight, weight gain and FCR compared to the control group. The villus:crypt ratio of both jejunum and ileum in all EP-treated groups was significantly higher than that of the control group. When testing serum antioxidant activity, results showed that 0.2% and 0.4% EP supplementation significantly increased superoxide dismutase activity in both the finisher phase and the overall experimental period. In addition, catalase activity was elevated in all EP supplemented groups in both the finisher phase and throughout the experimental period. 0.1% EP seemed to have no effect during the starter period. Serum malondialdehyde concentration was not affected by EP supplementation. These results suggest that EP is potential feed additive in terms of improving broiler performance and enhancing antioxidative status, while also providing an optimal intestinal environment.